2009
DOI: 10.1002/jmr.963
|View full text |Cite
|
Sign up to set email alerts
|

On the consequences of placing amino groups at the TBP–DNA interface. Does TATA really matter?

Abstract: The TATA-box binding protein (TBP) belongs to a family of structural proteins involved in transcription in eukaryotic cells. TBP binds in the minor groove of DNA and recognizes specifically the consensus sequence: 5' TATAWAWR 3' (W = A or T). Recent reports show that the TATA-box is only present in 10% of all human polymerase II promoters. Therefore, TBP must bind frequently to low affinity DNA sequences, possibly with help of other transcription factors. In order to understand the intramolecular and intermole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 78 publications
(112 reference statements)
0
0
0
Order By: Relevance
“…It is not established whether TBP association at TATA-less promoters drives similar degree of distortion (257). Mutational analyses have shown that single nucleotide alterations within the canonical TATA sequence can severely decrease the TBP-DNA binding affinity, suggesting that degenerate TATA-like sequences and TATA-less promoters may exhibit lower TBP affinity and, perhaps, lower degree of TBP intercalation as well (257,258). And while TAFs and TFIIA may compensate for this by stabilizing TBP onto the DNA, the possibility of differential DNA distortion based on the underlying TBP-bound sequence may be reflective of the dynamics of TBP turnover in post-initiation stage.…”
Section: Function: Promoter Binding Partners: Rnapi -Ii -Iii Pic Memb...mentioning
confidence: 99%
“…It is not established whether TBP association at TATA-less promoters drives similar degree of distortion (257). Mutational analyses have shown that single nucleotide alterations within the canonical TATA sequence can severely decrease the TBP-DNA binding affinity, suggesting that degenerate TATA-like sequences and TATA-less promoters may exhibit lower TBP affinity and, perhaps, lower degree of TBP intercalation as well (257,258). And while TAFs and TFIIA may compensate for this by stabilizing TBP onto the DNA, the possibility of differential DNA distortion based on the underlying TBP-bound sequence may be reflective of the dynamics of TBP turnover in post-initiation stage.…”
Section: Function: Promoter Binding Partners: Rnapi -Ii -Iii Pic Memb...mentioning
confidence: 99%